The impact of community-based monitoring on public service delivery: A randomized control trial in Uganda - Mogues, Tewodaj; Van Campenhout, Bjorn; Miehe, Caroline; Kabunga, Nassul (Elsevier, 2023)
In many developing countries, poor delivery of public services remains an important problem. Through community-based monitoring, beneficiaries of public services can apply bottom-up pressure to under-performing service providers and their political leadership. In this spirit, the Government of Uganda organizes community fora – popularly known as barazas – where citizens receive information from government officials and get the opportunity to challenge them. We designed a cluster randomized control trial to assess the impact of this policy intervention on public service delivery in agriculture, health, education, and infrastructure. We further test the relative importance of the two main components of the intervention—information provision and citizen engagement. We also compare the effectiveness of barazas organized at the district level to the effectiveness of barazas organized at the sub-county level. Following a pre-specified confirmatory analysis, we do not find that the intervention has significant effects on general public service delivery, even though public services in the agricultural sector do improve. We discuss some of the potential reasons for this finding, including assumptions underlying the impact pathways, the political context in which the program was implemented, and challenges related to the evaluation of large policy programs.